2022
DOI: 10.3233/jad-215345
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index and Mild Cognitive Impairment Among Middle-Aged and Older Adults from Low- and Middle-Income Countries

Abstract: Background: The effect of weight modification on future dementia risk is currently a subject of debate and may be modified by age. Objective: The aim of the present study was to investigate the association between body mass index (BMI) status with mild cognitive impairment (MCI) (a preclinical stage of dementia) in middle-aged and older adults residing in six low- and middle-income countries using nationally representative data. Methods: Cross-sectional data from the Study on Global Ageing and Adult Health (SA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…High body mass index (BMI) in midlife has been established as a modifiable risk factor for both MCI 4,5 and dementia. 6 However, the associations between late-life BMI and cognitive health remain unclear.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…High body mass index (BMI) in midlife has been established as a modifiable risk factor for both MCI 4,5 and dementia. 6 However, the associations between late-life BMI and cognitive health remain unclear.…”
mentioning
confidence: 99%
“…6 However, the associations between late-life BMI and cognitive health remain unclear. A few studies have reported that high BMI in late life is associated with dementia risk, 7,8 but others have shown that late-life obesity is either not significantly related to dementia [9][10][11] or associated with a decreased risk of MCI, 4,5 dementia, [12][13][14] and the progression from MCI to dementia. [15][16][17] These conflicting findings may be attributable to reverse causation because of weight loss preceding dementia.…”
mentioning
confidence: 99%
“…This study showed that a BMI of ≥ 25 kg/m 2 (obesity) was associated with a higher risk of MCI than was a normal BMI. A recent study of people aged 50 to 65 years also revealed that BMIs of < 18.5 and ≥ 25 kg/m 2 were associated with a higher risk of MCI [ 39 ]. However, the present study showed no association between BMI and a higher risk of dementia.…”
Section: Discussionmentioning
confidence: 99%